[Printing students] - Gus Beck::::::photographer::: (1942)
Charles Mendenhall, El Mustang editor, hand feeding the Whitlock Press in the Cal Poly Print Shop. This photo was included in El Rodeo Yearbook, 1942. Left to right: Charles Mendenhall, unidentified, Alfred Filipponi, unidentified, unidentified, and Jack Scheuer.